Apical CFTR Expression in Human Nasal Epithelium Correlates with Lung Disease in Cystic Fibrosis - van Meegen, Marit Arianne (Public Library of Science, 2013)
INTRODUCTION: Although most individuals with cystic fibrosis (CF) develop progressive obstructive lung disease, disease severity is highly variable, even for individuals with similar CFTR mutations. Measurements of chloride transport as expression of CFTR function in nasal epithelial cells correlate with pulmonary function and suggest that F508del-CFTR is expressed at the apical membrane. However, an association between quantitative apical CFTR expression in nasal epithelium and CF disease severity is still missing. METHODS AND MATERIALS: Nasal epithelial cells from healthy individuals and individuals with CF between 12–18 years were obtained by nasal brushing. Apical CFTR expression was measured by confocal microscopy using CFTR mAb 596. Expression was compared between both groups and expression in CF nasal epithelial cells was associated with standardized pulmonary function (FEV(1)%). RESULTS: The proportion of cells expressing apical CFTR in columnar epithelium is lower in CF compared to non-CF. The apical CFTR expression level was significantly correlated with FEV(1)% in F508del homozygous subjects (r = 0.63, p = 0.012). CONCLUSION: CFTR expression in nasal epithelial cells is lower in subjects with CF compared to healthy subjects. The proportion of cells expressing F508del-CFTR at the apical membrane is variable between subjects and is positively correlated with FEV(1)% in F508del-CFTR homozygous subjects.